2009
DOI: 10.1111/j.1365-2672.2009.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR study on the mode of action of oligosaccharide elicitors on penicillin G production by Penicillium chrysogenum

Abstract: Aim:  To investigate the effects of single and multiple additions of the oligosaccharide elicitors, obtained from alginate and locust bean gum, on penicillin G production and the transcript level of penicillin G biosynthetic genes. Methods and Results:  The transcript copy numbers and penicillin G concentration in liquid cultures of Penicillium chrysogenum grown under control and elicited conditions were compared using quantitative PCR and HPLC assay respectively. An increase in the penicillin G production rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…signatures were observed upon addition of OG or MO to E. coli pHCM05-Aq and B. subtilis pHCM05-Aq, suggesting that different calcium messages might be transmitted probably due to the difference in the three-dimensional structure between MO and OG. This may explain why higher antibiotic levels are achieved when P. chrysogenum and Bacillus licheniformis are stimulated with multiple elicitor additions using different elicitors (OG and MO) in comparison to repeated addition of the same elicitor to the culture (Murphy et al 2007b;Nair et al 2009). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…signatures were observed upon addition of OG or MO to E. coli pHCM05-Aq and B. subtilis pHCM05-Aq, suggesting that different calcium messages might be transmitted probably due to the difference in the three-dimensional structure between MO and OG. This may explain why higher antibiotic levels are achieved when P. chrysogenum and Bacillus licheniformis are stimulated with multiple elicitor additions using different elicitors (OG and MO) in comparison to repeated addition of the same elicitor to the culture (Murphy et al 2007b;Nair et al 2009). …”
Section: Discussionmentioning
confidence: 95%
“…Enhancement of penicillin G in elicited cultures may be related to the morphological changes caused by the elicitation (Radman et al 2004). Elicitors also effect the transcription of genes for antibiotic biosynthesis (Murphy et al 2007b;Nair et al 2009). However, a possible mechanism by which elicitors cause these changes has yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for these morphological changes are still speculative and require further investigation (Radman et al 2004). Recent studies have reported the enhancement of transcript copy number of the penicillin biosynthetic genes with a corresponding increase in the penicillin G production upon oligosaccharide elicitor (Nair et al 2009). There are initial reports of decrease in extracellular Ca 2þ levels on addition of mannan oligosaccharides (MO) as elicitors (Maria Teresa Saez Iturbe 2005).…”
Section: Introductionmentioning
confidence: 98%
“…A novel approach for enhancement of microbial metabolites is the use of elicitors. Elicitors are substances known to stimulate morphological and physiological responses when added in trace quantities to cultures (Radman et al 2003;Murphy et al 2007;Nair et al 2009). Previous reports of elicitation in Penicillium chrysogenum have reported an increase in hyphal-tip numbers, clump area and spore counts along with simultaneous increase in penicillin G production in elicitor-supplemented cultures.…”
Section: Introductionmentioning
confidence: 99%
“…These concentration changes serve as internal signals to direct the regulation of secondary metabolites via yet unknown mechanisms. An elicitor can either directly influence the transcription of the secondary metabolite gene cluster or induce a transcriptional activator of the target gene cluster (Kawai, Wang, 2007, Nair et al, 2009, Rigali et al, 2008, Tanaka et al, 2010.…”
mentioning
confidence: 99%